2020
DOI: 10.2147/dddt.s233932
|View full text |Cite
|
Sign up to set email alerts
|

<p>Metformin Activates the AMPK-mTOR Pathway by Modulating lncRNA <em>TUG1</em> to Induce Autophagy and Inhibit Atherosclerosis</p>

Abstract: Background: Metformin has been shown to inhibit the proliferation and migration of vascular wall cells. However, the mechanism through which metformin acts on atherosclerosis (AS) via the long non-coding RNA taurine up-regulated gene 1 (lncRNA TUG1) is still unknown. Thus, this research investigated the effect of metformin and lncRNA TUG1 on AS. Methods: First, qRT-PCR was used to detect the expression of lncRNA TUG1 in patients with coronary heart disease (CHD). Then, the correlation between metformin and TUG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…AMPK/mTOR is the important modulator of cellular autophagy. Hepatic protein kinase B1 is able to activate AMPK in some circumstances such as starvation and energy consumption, which negatively regulates mTOR [ 30 ]. It has been reported that lowered expression of p-mTOR induced by AMPK phosphorylation is capable of facilitating autophagy in a variety of cell types [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMPK/mTOR is the important modulator of cellular autophagy. Hepatic protein kinase B1 is able to activate AMPK in some circumstances such as starvation and energy consumption, which negatively regulates mTOR [ 30 ]. It has been reported that lowered expression of p-mTOR induced by AMPK phosphorylation is capable of facilitating autophagy in a variety of cell types [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“… 21 Furthermore, AMPK activation by 5-aminoimidazole-4-carboxamide ribonucleotide was reported to inhibit the mTOR/p70S6K signaling pathway in human umbilical vein endothelial cells (HUVECs) and VSMCs. 22 23 Most recently, it was reported that valsartan increased p-AMPK-Thr 172 level and decreased p-mTOR-Ser 2448 level in rat VSMCs 24 ; however, there were somewhat inconsistent time-course results between AMPK activation and mTOR inhibition, i.e., the decreases in p-mTOR-Ser 2448 occurred before the increase in p-AMPK-Thr 172 . 24 Unlike the recently reported data, in the current study, we observed that telmisartan increased AMPK activity first (at 6 hours of treatment) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were randomly divided into high‐fat diet group ( n = 6) and normal feeding group ( n = 6) after adaptive feeding for a week. A rat model of AS was established as previously described (You et al, 2020), and the high‐fat feed ingredients were 80.8% normal diet + 0.2% propylthiouracil + 0.5% sodium cholate + 3.5% cholesterol + 5% sugar + 10% lard. In addition, rats were fed with vitamin D3 (700,000 U/kg) via gavage for three times.…”
Section: Methodsmentioning
confidence: 99%